2021
DOI: 10.1108/jhom-01-2021-0008
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of the concept of person-centred care into discourse in Europe: a systematic literature review

Abstract: PurposeThis study aims to describe how person-centred care, as a concept, has been adopted into discourse in 23 European countries in relation to their healthcare systems (Beveridge, Bismarck, out of pocket).Design/methodology/approachA literature review inspired by the SPICE model, using both scientific studies (CINHAL, Medline, Scopus) and grey literature (Google), was conducted. A total of 1,194 documents from CINHAL (n = 139), Medline (n = 245), Scopus (n = 493) and Google (n = 317) were analysed for conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 29 publications
(60 reference statements)
1
39
0
Order By: Relevance
“…Furthermore, the highest rating of perceived collaboration was on the subscale Trust and its prerequisites . The results might be an expression of person-centred care, a policy and criterion for quality of care applied for more than a decade in Sweden [ 35 ]. Person-centred care implies that the patient is viewed as a person with resources and abilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the highest rating of perceived collaboration was on the subscale Trust and its prerequisites . The results might be an expression of person-centred care, a policy and criterion for quality of care applied for more than a decade in Sweden [ 35 ]. Person-centred care implies that the patient is viewed as a person with resources and abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Person-centred care implies that the patient is viewed as a person with resources and abilities. Such care is characterised by listening to what the person has to say and by partnership and agreement between the patient, family and healthcare professionals regarding interventions [ 35 , 36 , 37 ]. Since collaboration is part of person-centred care, the FCS should be tested as an outcome measure in the implementation of person-centredness in practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-management has also been described as a fundamental part of person-centered care [ 13 ], which aims to give people opportunities to improve and manage their health according to their beliefs, values, and preferences. Person-centered care also supports the premise that people should be given tools and strategies to recognize and develop their strengths and abilities to live independent and satisfying lives as much as is possible [ 14 - 16 ]. In that sense, the concept of person-centered care is strongly related to person-centered self-management support, which prioritizes and encourages patients to define their health outcomes according to what is most meaningful and important [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing trend towards person-centred care (PCC) throughout the world, advocated by different stakeholders, including the World Health Organization (WHO), patients, relatives and health care professionals (HCPs) [1][2][3][4]. Different definitions and understandings of PCC exist, with the common denominator being mutual respect and co-creation of health and care where the patient is an active partner in and not a passive recipient of care [4,5]. Studies have found that PCC improves patients' health [6], staff 's work satisfaction and health [7], and that it is financially viable [8,9].…”
Section: Introductionmentioning
confidence: 99%